Gaining insight into Tua railway line through interactive experiments - Esteves, João Sena (2012)
In the framework of FOZTUA Project, several initiatives are being planned in order to disseminate the natural environment and history of Tua Valley and Tua railway line. This paper presents some interactive experiments that are being designed for Openlab, a museological-like place under development within FOZTUA Project. These experiments will allow visitors to gain insight into the main features of the Tua line, some of which are also described in the paper.